2021
DOI: 10.1080/2162402x.2021.1898753
|View full text |Cite
|
Sign up to set email alerts
|

Re-polarization of immunosuppressive macrophages to tumor-cytotoxic macrophages by repurposed metabolic drugs

Abstract: M2-like tumor-associated macrophages promote tumor progression by establishing an immunosuppressive tumor microenvironment. The phenotype and activity of immunosuppressive macrophages are related to their mitochondrial metabolism. Thus, we studied if drugs targeting mitochondrial metabolic pathways can repolarize macrophages from M2 into an M1-like phenotype or can prevent M0-to-M2 polarization. The drugs selected are clinically approved or in clinical trials and target M2-specific metabolic pathways: fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…This metabolic plasticity is also a major feature found in macrophages. Classically, M1 capture their energy from glycolysis, fatty acid synthesis, and the pentose phosphate pathway, whereas M2 make extensive use of glutaminolysis and fatty acid oxidation to fuel oxidative phosphorylation [ 22 , 57 ]. A recent study reported that glutamine deprivation prevented IL-4 mediated polarization, highlighting the importance of glutaminolysis metabolism for M2 polarization [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic plasticity is also a major feature found in macrophages. Classically, M1 capture their energy from glycolysis, fatty acid synthesis, and the pentose phosphate pathway, whereas M2 make extensive use of glutaminolysis and fatty acid oxidation to fuel oxidative phosphorylation [ 22 , 57 ]. A recent study reported that glutamine deprivation prevented IL-4 mediated polarization, highlighting the importance of glutaminolysis metabolism for M2 polarization [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…At least in preclinical CRC models, such an immunosuppressive pathway is initiated by the CAF-driven, CXCL8-dependent polarization of TAMs towards an M2-like phenotype [ 191 ]. M2-like TAMs collected from the ascites of patients with ovarian cancer and exposed to Toll-like receptor (TLR) ligands appear to undergo repolarization towards an M1-like state, resulting in IL12 secretion and acquisition of cytolytic functions by co-cultured NK cells [ 192 , 193 ]. Finally, monoclonal antibodies targeting scavenger receptors on M2-like TAMs have been shown to limit their immunosuppressive effects and efficiently derepress the cytolytic functions of NK cells in human and mouse models of melanoma [ 194 ].…”
Section: Immunological and Stromal Barriers Against Nk Cell Activitymentioning
confidence: 99%
“…Based on their polarization fate, they can be divided into the M1 (pro-inflammatory) and M2 (anti-inflammatory) phenotypes. Interestingly, M1 and M2 cells can repolarize to each other depending on the interventions administered (for example, by targeting mitochondrial metabolic pathways) ( 41 43 ). Numerous studies have reported the supportive effects of TAMs on malignant cells in the CRC TME.…”
Section: Mechanisms Of Immunotherapy Resistancementioning
confidence: 99%